Reform-Press . Reform-Press . Reform press . Реформ-Пресс - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A program about the family and the private life of the politician Egor Gaidar. Featured in the program: Gaidar, Egor Timurovich (Deputy of the State Duma) Программа о семье и частной жизни политика Егора Гайдара. В программе участвуют: Гайдар, Егор Тимурович (Депутат Государственной Думы)